2006
DOI: 10.1002/tee.20033
|View full text |Cite
|
Sign up to set email alerts
|

Portable application of thermal plasma and arc discharge for waste treatment, thermal spraying and surface treatment

Abstract: Thermal plasma and arc discharge have numerous useful characteristics related to their high temperature and intense radiation. Many applications have been developed. Recently, a portable twin-torch plasma arc furnace for waste treatment, thermal spraying torches, steam plasma torches, and surface treatment of low-pressure arc was developed. This paper describes the recent development of a portable application of thermal plasma and arc discharge. The portable device can treat wastes and perform thermal spraying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Thermal plasma technology has been applied in various industrial applications such as cutting, welding, spraying, metallurgy, mass spectroscopy, nano-sized particle synthesis, powder spheroidization, and waste treatment [12][13][14][15]. Over the past decade, thermal plasma process has also been regarded as a viable alternative to treat highly toxic wastes, such as air pollutant control (APC) residues, radioactive, and medical wastes [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal plasma technology has been applied in various industrial applications such as cutting, welding, spraying, metallurgy, mass spectroscopy, nano-sized particle synthesis, powder spheroidization, and waste treatment [12][13][14][15]. Over the past decade, thermal plasma process has also been regarded as a viable alternative to treat highly toxic wastes, such as air pollutant control (APC) residues, radioactive, and medical wastes [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the vitrification of radioactive waste, medical waste, metal-rich sludge, and incinerator fly ash have shown that thermal plasma is a promising technology and particularly well suitable for hazardous waste treatment. It offers the predominant characteristics of high temperature and high energy density, which allows for effective heat transfer at the reactor boundaries and corresponding fast reaction times during the waste processing. , In the past decade, plasma-based vitrification processes for incineration residues have been extensively developed at laboratory and pilot scales. The most widely used arc plasma sources in these processes are transferred arc or nontransferred arc plasma torch. One example of the demonstrated vitrification system for incinerator fly ash immobilization is provided by Europlasma .…”
Section: Introductionmentioning
confidence: 99%